Boosting Room Temperature Phosphorescence Performance by Alkyl Modification for Intravital Orthotopic Lung Tumor Imaging. Issue 22 (18th February 2021) - Gao, Heqi; Gao, Zhiyuan; Jiao, Di; Zhang, Jingtian; Li, Xiaolin; Tang, Qiyun; Shi, Yang; Ding, Dan
Abstract: Pure organic persistent room temperature phosphorescence (RTP) materials have attracted wide attention owing to their great potential in various applications, particularly in bioimaging. However, it is still a challenge to manufacture organic RTP materials possessing quite high efficiency and long lifetime, owing to the high requirements for triplet excitons. In this study, a series of keto derivatives with efficient RTP in crystals are developed through the regulation of molecular aggregation states by simple alkyl groups, resulting in impressive luminescence performance with a longer lifetime and higher efficiency of up to 868 ms and 51.59%, respectively. All the alkyl‐substituted derivatives exhibit bright RTP intensities after heavy grinding with a pestle, indicating their robust RTP features, which are suitable for many fields. Encouraged by the excellent RTP performance of these luminogens in the crystalline state, successful orthotopic lung tumor imaging with a high signal‐to‐background ratio (SBR) of 65 is demonstrated in this study to provide the promise of pure organic RTP materials for disease diagnosis, which hold the advantages of low autofluorescence interference and high signal‐to‐background ratio. Abstract : Regulating molecular aggregation to improve the luminescent efficiency and room temperature phosphorescence lifetime is demonstrated by a simple alkyl modification strategy. The resultant crystalline nanoparticles can selectively light up orthotopic lung tumors via room temperature phosphorescence after intravenous administration into pulmonary metastatic carcinoma‐bearing mice, showing a rather high signal‐to‐background ratio of 65.